Effect of Escalated Doses of Gamma Radiation in Combined Radiation and Wound Injury Animal Model - Gupta, Varsha (My University, 2023)
Radiation exposure events on a large scale have always found that victims exposed to radiation are also often suffering from other injuries including blast, burns, or wounds. These types of injuries are known as combined radiation injuries (CRI). CRI is an extremely harmful and deadly form of trauma and multiple studies suggest that conventional trauma and radiation injury have detrimental synergistic effects on the victim. CRIs are known to dramatically increase mortality and delayed wound healing. To study the effect of interventions against combined injuries, the animal model needs to be developed. In this study, the efforts have been made to develop the CRI model in experimental rats (Sprague Dawley) by exposing the animal to different doses of ionizing radiation (60Co-gamma rays: 5Gy and 6Gy) followed by the creation of dermal wounds (excision wound) on the dorsal skin surface. Animals were then observed for changes in body weight, wound area, and wound score. Further the changes in the hematopoietic system, and inflammation were determined in skin and blood tissues in animals exposed to CRI. The study showed that with the increase in radiation doses, there was a decrease in survival rate and delayed wound healing. CRI increased the body weight loss, suppressed hematopoiesis, produced systemic inflammation, and damaged bone marrow at various doses (5 Gy and 6 Gy) on days 0, 7, 15, and 30. In conclusion, the results of our study indicated that decrease in survival rate and impaired wound healing was radiation dose-dependent.
Keywords: Wound injury; Gamma Radiation; Inflammation; Doses